La controverse sur l’inclusion des femmes dans le système fiscal romain pendant la République : (195 av. n. è. – 39 av. n. è.) - Lizarzategui, Leire (Studia Historica. Historia Antigua, 2022)
Though ancient sources mention some exceptions, Roman women were exempt from paying the tributum, the most onerous of direct taxes. It was only in the aftermath of the Second Punic War when some senators tried to sustain a war measure (the lex Oppia) that limited their access to riches. Such attempt forced Roman women into a public protest in 195 BC, which received a considerable support from many citizens. For the next 150 years the Romans sustained, although with irregular intensity, a social debate on whether it was just or not to include women in their fiscal system as regular taxpayers. When referencing to such debate ancient sources focus mainly on the moral relevance of those measures. However, considering that during those turbulent years of the late Republic marriage practices and the morphology of the elite groups also changed, we shall propose that such debate answered to rather more pragmatic considerations.